Comparative analysis of the results of laparoscopic and classical hepatic resections for multiple tumors in patients with hepatocellular carcinoma - Aleksander Tarasik (PAGEPress Publications, 2024)
Laparoscopic removal of the affected part of the organ and classic laparotomic resection with open access for surgical manipulations are widespread. The choice of resection method is still controversial because researchers are currently talking about the importance of minimally invasive surgical techniques. The purpose of this study was primarily to compare the intraoperative, early, and late postoperative status of patients who underwent laparoscopic or laparotomic hepatic resection for multiple foci of hepatocellular carcinoma. In general, the operations using the laparoscopy method are much safer, because perioperative complications (including intense stress reactions with the appearance of hypertension, suppression of the immune response, tachycardia, and hypercoagulability) occur much less frequently than in the case of open-access intervention. Less invasiveness of laparoscopic operations contributes to a better recovery of patients after resection. On the other hand, laparotomy provides wider and faster access to the liver. This meta-analysis compares the effectiveness of minimally invasive laparoscopic resections over classic laparotomic operations in patients diagnosed with hepatocellular carcinoma with multiple tumors.